Product Scarcity Strategy And Price Promotion To Purchase Intention: An Inverted U-Shaped Relationship - Harimurti Wulandjani; Supriadi Thalib; Dian Riskarini; Amelia Oktrivina (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2023)
The existing literature suggests that the scarcity signal is a crucial factor that determines consumer purchase intention. However, research inconsistencies regarding the direction of the relationship require more attempts to understand whether there is a possible inverted U-shaped relationship between scarcity and purchase intention. Moreover, this study examines the role of price promotion as a boundary condition. This study aims to shed light on the scarcity signal–online purchase intention relationship in a sample of students in Jakarta. The results show an inverted U-shaped relationship between scarcity and purchase intention. In addition, the interaction of price promotion and scarcity signals appears to be particularly important for yielding higher purchase intention. The implications of these findings contribute to the literature on online purchase decisions and allow online marketers to evaluate marketing strategies, especially in online markets.